Cytogenetic Effects Of Fumagillin On Male Mice (Mus musculus) - Wajdi Sabeeh Sadeq; Asaad Abed-Elwahed Bader; Yazan Ali Taha (Tikrit Journal of Pure Science)
The cytogenetic effects of Fumagillin were evaluated according to Mitotic Index (M.I) and aberration of metaphase chromosomes in bone marrow cells(CA) of white mice. The fumagillin was given as repeated oral gavages for 7 successive days after preparing the doses 10,15 at concentrations 20 mg/kg.b.wt. in 50% of sugar syrup . The positive control was given single I.p. dose of  20 mg/kg.b.wt. of methotrexate. The three dosages 10, 15, and 20 mg/kg.b.wt of Fumagillin induced significant decrease in mitotic index (3.90 ± 0.29, 3.60 ± 1.80, and 2.90 ±0.18) respectively compared with (7.10 ±0.29) for negative control. The results showed that the two dosages 15 and 20 mg/kg.b.wt of Fumagillin induced significant increase in the frequency of the chromosome aberration in bone marrow cells of the mice in the these groups (9.00± 0.92, 17.20 ± 1.42) respectively compared with (6.00 ±0.83) for negative control. The obtained result revealed the genetic and cellular toxic reaction of Fumagillin within the high and medium  limits studied doses.